Optimizing Students’ Reading Comprehension Through Direct Reading Thinking Activity - sulaiman sulaiman (Universitas Majalengka, 2019)
The research was conducted in order to know how Direct Reading Thinking Activity improve students’ reading comprehension This research was done by using the Classroom Action Research method to solve the problems faced by the students. This research was conducted at the second-semester students of Islamic Education Study Program in IAIN Pontianak. The researcher used purposive sampling as the sampling technique by choosing class D consisting of 24 students as the sample of the research.After the result of the test had been calculated and analyzed by the researcher, the result showed the mean score for the first cycle was 67, and 72 in the second cycle. The students also showed a positive response during the implementation of Direct Reading Thinking Activity in teaching reading comprehension. It can be indicated that the students’ achievement in reading comprehension had been improved through Direct Reading Thinking Activity.Based on the result above, the researcher concluded that Direct Reading Thinking Activity can improve students’ reading comprehension well. The researcher suggested to the other teachers who want to teach the students with the material of reading comprehension, Direct Reading Thinking Activity is appropriate to be used in improving students’ achievement.